Mediating role of task-related affective well-being in the influence of customer participation via self-service technologies on service outcomes - Asokan Ajitha, Aswathy (Curtin University, 2020)
The study focuses on the role of task-related affective well-being in the influence of customer participation on service outcomes and the differential impact of customer participation types. Also, the study considers the critical intervention of customer knowledge and task complexity. A scenario-based experimental design was conducted in Indian domestic airlines check-in service encounter and Australian supermarket checkout service encounter. The study advances the extant literature and provides several managerial implications.